The Problems of Evaluation of Islamic Religious Education Learning After Online Learning During The Covid-19 Period - Irfa Miswanti; Aguswan Rasyid; Mayudin Ritonga (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study examines the problems of evaluating Islamic Religious Education learning in face-to-face learning after online learning during the Covid-19 pandemic at SD Negeri 11 Pudung. This study aims to describe the implementation of PAI learning, the factors supporting and inhibiting the implementation of PAI learning evaluation, as well as efforts to increase the effectiveness of the implementation of PAI learning evaluation after online learning during the pandemic. The study adopted a qualitative approach based on descriptive methods. Sources of data were collected from primary and secondary data sources. Data collection is oriented to the technique of observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing, while the data validity test used source triangulation. The results showed that the implementation of PAI learning evaluation after online learning at SD Negeri 11 Pudung was carried out referring to a series of predetermined learning evaluation procedures including the evaluation planning stage, the evaluation implementation stage, and the processing, reporting, and utilization stages of the evaluation results. Factors supporting the implementation of PAI learning evaluation include teacher competency factors, students' internal conditions, and the availability of learning resources, while the inhibiting factors for its implementation are related to the number of classes and students that must be handled by the teacher, limited time allocation, and parental care. Efforts to improve the effectiveness of the implementation of PAI learning evaluation are carried out by building synergies between teachers and parents, developing alternative assessments, and supporting school principals.